The present and future of PSM under austerity: the case of CYBC - Spyridou, Lia Paschalia; Milioni, Dimitra L. (ORF, 2014)
Historically, the media sector in Europe has been based on a duopoly allowing for mutual competition between the public and the private media. Lately, major politico-economic shifts supporting the market logic and its doctrines have signalled a serious retreat from active public sector to privatizations. In that context, Public Service Media (PSM) is undergoing detailed scrutiny and criticism. Unsurprisingly, in countries more severely hit by the current ﬁnancial crisis, the debate over the role, remit and funding of PSM has intensiﬁed. At the same time, rapid tech-nological changes have been driving the transition of the traditional Public Service Broadcasters (PSBs) into Public Service Media (PSM), making public service content available in multiple platforms (Iosiﬁdis, 2011).
Keywords: Public service media; Public service broadcasters; Cyprus Broadcasting Corporation